Influencia de las tecnologías de autoservicio en la experiencia del consumidor en los principales supermercados - Cárdenas Becerra, Mariel Ivette (2022)
This investigation is based in the study of the new self-service technologies installed in retail supermarkets, the aim is to observe the customer acceptance, the benefits associated with the use of this technology, ease of use, interactions, waiting time, but especially the perceived quality by customers because this will help develop a positive customer experience and will motivate them to go back to that store and use the technology again. In addition to this, we examined the store environment, the perceptions and the customer preferences at the moment of use because the customers rather make use of this technology by their own without any human help, it makes them feel with more control of the situation and they do not feel comfortable when somebody is looking at them. Therefore, it can be confirmed the factors of this technology which are short waiting time, autonomy, and the efficiency. However, some studies have shown that the main reason why some customers have not wanted to use this technology is because they are afraid of the unknown and they are used to the traditional process. Ultimately, it does not exist demographic differences between a user and a non-user and that it is important to focus on a target that it is likely to use this kind of technology and offer them facilities at the moment of use. The businesses should pay more attention to customer behavior because they are not used to express themselves, so that will help in created new tools for a great customer experience.